THE EFFECT OF READ, COVER, REMEMBER, RETELL (RCRR) STRATEGY.ON STUDENT’S READING SKILL THROUGH NARRATIVE TEXT AT SMA NEGERI 3 BARRU - Ikram Agus; Uyunnasirah Hambali; Sitti Maryam Hamid (FKIP Unismuh Makassar, 2022)
This.research aims to determine the effect of using the RCRR strategy on students'.reading ability. This research method is quantitative with a pre-experimental design.The subjects of this study were eleventh graders consisting of 20 students. 20 students in class XI MIPA 2 as an experimental class. The instrument used in this study was a multiple choice test. The test is given in the form of a pre-test..and a post-test. From the results of the analysis, the researcher indicates that the results of the average post-test score of the experimental class (78.50) are higher than the average value of the pre-test (52.25) obtained by students in the experimental class, so H0 is rejected and Ha1 acceptable. This means that there is a significant effect after the strategy treatment (RCRR).The increase in pre-test and post-test was 50.23%. Furthermore, the researcher has analyzed the t-test value, t-test t-table (18.763 ≥ 1.729) is greater than the t-table value. That is, there.is.a significant effect on the reading ability of.students who use the RCRR strategy taught in the eleventh grade MIPA 2 SMA Negeri 3 Barru.